2017
DOI: 10.4269/ajtmh.16-0559
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Antibody Responses as a Measure of Exposure to Malaria in the Indigenous Batwa and Their Non-Indigenous Neighbors in Southwestern Uganda

Abstract: Abstract. Understanding variations in malaria transmission and exposure is critical to identify populations at risk and enable better targeting of interventions. The indigenous Batwa of southwestern Uganda have a disproportionate burden of malaria infection compared with their non-indigenous neighbors. To better understand the individual-and community-level determinants of malaria exposure, a seroepidemiological study was conducted in 10 local council cells in Kanungu District, Uganda, in April 2014. The Batwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…1 ), where they relied on subsistence hunting and gathering; eviction from the park forced them into settlement in agrarian communities outside the park boundaries (19). There are currently approximately 6700 Batwa individuals living in southwestern Uganda [ 20 ], 900 of whom live within Kanungu District. There are no notable ecological or geographic differences in the areas where the Batwa or Bakiga live that would increase risk of malaria in either population (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1 ), where they relied on subsistence hunting and gathering; eviction from the park forced them into settlement in agrarian communities outside the park boundaries (19). There are currently approximately 6700 Batwa individuals living in southwestern Uganda [ 20 ], 900 of whom live within Kanungu District. There are no notable ecological or geographic differences in the areas where the Batwa or Bakiga live that would increase risk of malaria in either population (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the underlying risk factors for this high prevalence among Batwa have been linked to relative poverty, not owning a bed net, iron sheet roofing with openings for mosquito entry, not avoiding mosquito bites, malnutrition, stagnant water and bushy environment around homesteads [16] [17] [23] [48]. Relatedly, [43] strongly suggested that indigenous Batwa in Kanungu are a population at heightened risk of malaria exposure and infection. After adjusting for age, infection status, elevation, and clustering by villages, [43] found that the Batwa had two-fold higher odds of being malaria seropositive compared with the Bakiga (OR = 2.08, 95% CI = 1.51 -2.88).…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, [43] strongly suggested that indigenous Batwa in Kanungu are a population at heightened risk of malaria exposure and infection. After adjusting for age, infection status, elevation, and clustering by villages, [43] found that the Batwa had two-fold higher odds of being malaria seropositive compared with the Bakiga (OR = 2.08, 95% CI = 1.51 -2.88). In line with this study, it was discovered that majority of Batwa 76.6% (n = 408) did not sleep under any net, and 58% did not sleep under an ITN the night prior to the survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Batwa community, self-identified as Indigenous, lives in south-western Uganda and represents a minority group in Kanungu District (14) . The Bakiga community resides in the same area and constitutes the majority population in the district (15,16) . The Batwa were originally hunter-gathers until their displacement in 1991 from the forest, now known as Bwindi Impenetrable National Park (17) .…”
Section: Study Region and Populationmentioning
confidence: 99%